1999
DOI: 10.1111/j.1348-0421.1999.tb02472.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Murine Collagen‐Induced Arthritis Using Klebsiella pneumoniae O3 Lipopolysaccharide as a Potent Immunological Adjuvant

Abstract: Collagen-induced arthritis (CIA) was produced in mice with non H -2q and H-2r haplotypes by repeated immunization of porcine type-II collagen (CII) together with Klebsiella O3 lipopolysaccharide (KO3 LPS) as an immunological adjuvant. Histological changes that appeared in joints of repeatedly immunized mice were characterized by destruction of normal joint structure, synovial hyperplasia with proliferation of synovial cells, and infiltration of inflammatory cells. No such lesions were produced in mice receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…In the present study, we detected a second increase in gene expression of some inflammatory mediators 2-8 hrs after LPS injection, this interval of time being just after the increase in serum anti-CII IgG. Additionally, a previous study has shown that LPS injection of mice without CII immunization does not induce arthritis (23,26). Thus, production of anti-CII antibody and the consequent induction of continuous expression of inflammatory mediators may be necessary for acute onset of LPS-CIA.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study, we detected a second increase in gene expression of some inflammatory mediators 2-8 hrs after LPS injection, this interval of time being just after the increase in serum anti-CII IgG. Additionally, a previous study has shown that LPS injection of mice without CII immunization does not induce arthritis (23,26). Thus, production of anti-CII antibody and the consequent induction of continuous expression of inflammatory mediators may be necessary for acute onset of LPS-CIA.…”
Section: Discussionsupporting
confidence: 69%
“…Required for leukocyte endothelial interactions in vivo [78] Eosinophils Expression of MIF [6] Expression of MIF [79,80] B lymphocytes Growth factor [76,81] Expression of MIF [70] Induce cPLA2, COX-2, IL-1, IL-6, IL-8, MMPs [52,82,84] Induce proliferation, inhibit apoptosis [23,85] Synovial or other fibroblasts Activate MAP kinases [47,85] gen-induced arthritis model [21]. In this study, neutralisation of MIF using a monoclonal antibody resulted in delayed onset and lowered frequency of arthritis.…”
Section: Mif Is a Pro-inflammatory Mediator In A Range Of Immune-medimentioning
confidence: 99%
“…Collagen-induced enterocolitis [42] as well as arthritis [43] has been observed in experimental animals when immunized with homologous colonic extracts and collagen type II together with Klebsiella lipopolysaccharides.…”
Section: Aetiopathogenesismentioning
confidence: 99%